Pre-Assembly Core Loss Measurement of Electric Motor Cores: A Review of Conventional and Advanced Technologies - Sudesh V. Pathirannahalage; Lukasz Mierczak; Berker Bilgin (IEEE Access)
Accurate core loss measurement considering manufacturing effects is essential for improving motor efficiency and reliability. This paper explores pre-assembly core loss measurement techniques in electric motors, focusing on the influence of manufacturing processes and the efficacy of core loss measurement methods. Traditional methods such as the Epstein frame, Single Sheet Tester (SST), and toroidal core measurement are discussed, along with recent advancements in measurement techniques. Experimental methods with an excitation yoke placed inside a stacked stator for core loss measurement, mainly under an alternating magnetic field, are presented. The application of advanced core loss measurement in industrial settings highlights that automation plays a vital role in enhancing measurement efficiency. The gaps in the existing literature and specific areas where further research is needed are discussed.